2018
DOI: 10.1016/j.stem.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Autologous iPSC-Based Vaccines Elicit Anti-tumor Responses In Vivo

Abstract: Cancer cells and embryonic tissues share a number of cellular and molecular properties, suggesting that induced pluripotent stem cells (iPSCs) may be harnessed to elicit anti-tumor responses in cancer vaccines. RNA-sequencing revealed that human and murine iPSCs express tumor-associated antigens, and we show here a proof-of principle for using irradiated iPSCs in autologous anti-tumor vaccines. In a prophylactic setting, iPSC vaccines prevent tumor growth in syngeneic murine breast cancer, mesothelioma, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 54 publications
5
127
1
Order By: Relevance
“…Very recently, Kooreman et al [28] demonstrated that murine autologous fibroblast-derived miPSC-based vaccines generated anticancer immunity against various types of cancers, including melanoma, breast cancer and mesothelioma. They based their studies on the thesis that iPSCs and cancer cells share a broad spectrum of epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Kooreman et al [28] demonstrated that murine autologous fibroblast-derived miPSC-based vaccines generated anticancer immunity against various types of cancers, including melanoma, breast cancer and mesothelioma. They based their studies on the thesis that iPSCs and cancer cells share a broad spectrum of epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible to induce immune responses toward normal tissues. Nigel et al did not observe autoimmunity after treatment with autologous iPSC vaccine [11]; however, further investigation needs to be carried out to confirm the safety of the approach.…”
Section: Increased Immune Responses and Autoimmunitymentioning
confidence: 97%
“…These iPSCs share the same characteristics with ESCs while removing ethical concerns from embryo destruction. Till now, both hESCs and iPSCs are important sources for the induction of effector T-and NK cells [7][8][9][10], and for the production of anti-cancer vaccines [11,12], which will be discussed later in this review.…”
Section: Pluripotent Stem Cells (Pscs)mentioning
confidence: 99%
See 2 more Smart Citations